An Exact Feedback Linearization Control of a SMES System to Support Power in Electrical Grids (2018)
This paper presents an exact feedback linearization control strategy to operate superconducting magnetic energy storage (SMES) systems connected to an electric distribution network through a pulse-width-modulated current source converter (PWM-CSC). To model this system an average model is employed by using dq reference frame. The dynamical model of the SMES system considering the PWM-CSC is transformed algebraically into an equivalent linear model by simple substitutions, avoiding to use an equivalent linearization technique or Taylor's series. The linear model preserves all features of the nonlinear model, which allows obtaining control laws to be applicable in its non- linear system. The proposed control scheme permits the active and reactive control of the SMES system in a wide range of operating independently. The effectiveness and the robustness of the proposed control methodology are tested in a low-voltage distribution network considering unbalance and high harmonic distortion in the voltage provided by the utility. All simulation cases are carried out in MATLAB/ODE environment under time domain reference frame, and they are compared with a conventional PI controller. © 2018 IEEE.